2020
DOI: 10.1002/jtr.2425
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Chinese households' tourism consumption: Evidence from China Family Panel Studies

Abstract: Using survey data from the China Family Panel Studies project, this study explores factors influencing Chinese households' tourism consumption. The Heckman model is employed to decompose households' travel decision-making process into two stages: first deciding whether to engage in travel and tourism and then determining the level of tourism consumption. We find that sociodemographic, economic, and psychological factors shape Chinese households' tourism consumption. Our results paint a vivid picture of Chinese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 40 publications
4
22
0
1
Order By: Relevance
“…From these results, it is clear that demographic characteristics as expressed by gender, marital status, age, income, and level of education are all significant in determining travel decision of domestic tourists. These findings were supported by a previous studies such as (Jessen, 2011;Ndivo, 2012;USAID, 2013;Kihima, 2015;Beirmin, 2016;Njagi, 2017;Aziz, et al, 2018;KNBS, 2019;WTTC, 2019;KNBS, 2020;Lin et al, 2020;Mkwizu, 2020;.…”
Section: Chi-square Statistical Test Of Demographic Versus Travel Cha...supporting
confidence: 88%
See 2 more Smart Citations
“…From these results, it is clear that demographic characteristics as expressed by gender, marital status, age, income, and level of education are all significant in determining travel decision of domestic tourists. These findings were supported by a previous studies such as (Jessen, 2011;Ndivo, 2012;USAID, 2013;Kihima, 2015;Beirmin, 2016;Njagi, 2017;Aziz, et al, 2018;KNBS, 2019;WTTC, 2019;KNBS, 2020;Lin et al, 2020;Mkwizu, 2020;.…”
Section: Chi-square Statistical Test Of Demographic Versus Travel Cha...supporting
confidence: 88%
“…Recent studies, noted that 42.1% of domestic tourists prefer Kenyan coast due to the divergent touristic resources (KNBS, 2019). However, in contrast a previous noted that single persons are likely to engage in tourism activities since they have no strenuous family obligations in comparison with married couples (Lin et al, 2020). In spite of such observations Kenyan coast continuous as a progressive and competitive destination due to the uniqueness of its touristic attractions.…”
Section: Demographic Informationmentioning
confidence: 88%
See 1 more Smart Citation
“…These results implied that China's current tourism industry demonstrated a new feature that a transition from sightseeing tourism to leisure and holiday tourism is very much likely to occur. Meanwhile, residents' affluence has been highlighted as an indispensable contributor to nationwide tourism development [59]. Under such a changing background of the tourism industry in China, it is highly suggested that improving personal income, as well as safeguarding the rights and interests of employees, should be adopted as an essential strategy for facilitating the nationwide tourism industry development, which might be achieved via the implementation of multiple tourism-related policies at governmental levels, such as approving paid-leave policies for employees, encouraging enhanced flexibilities of work schedules to be tailored for vocational leaves, as well as encouraging off-peak vocational arrangements.…”
Section: Discussionmentioning
confidence: 99%
“…Частное социальное доверие возникает на близком социальном расстоянии по отношению к людям, знакомым в повседневном взаимодействии. Считается, что чем сильнее общее доверие, т. е. доверие к незнакомым людям, тем выше мотивация в туристском путешествии и выше расходы [22]. Cемейный туризм имеет более сильное внутригрупповое социальное доверие, что может давать большую уве-ренность при совершении неизвестных культурно-досуговых активностей.…”
unclassified